Keloids of the Ear - P. A. Thomas (Indian Journal of Plastic Surgery, 1971)
Keloids of the ear particularly lohule are suitable Tor excision. Pre-operative and post-operative irradiation helps 1o reduce the incidence of recurrence of keloid.